2001
DOI: 10.1021/jp003453z
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Single-Wall Carbon Nanotubes

Abstract: A purification method has been developed that provides for the removal of metal catalysts and impurity carbon from laser-oven-grown single-wall carbon nanotube (SWNT) material. The oxidation rate of SWNTs in air at elevated temperatures is correlated to the metal content of the sample. Sample purity is documented with SEM, TEM, electron microprobe analysis, Raman, and UV-vis-near-IR. We also note that the relative intensity of the electronic transitions in the near-infrared to the continuum absorption at 400 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
400
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 528 publications
(421 citation statements)
references
References 36 publications
15
400
0
6
Order By: Relevance
“…One efficient dry purification technique is oxygen burning, or annealing, in which oxygen gas preferentially oxidizes both amorphous carbon and sp 3 -hybridized carbon nanoparticles, which are more reactive than sp 2 -hybridized SWNTs. 41,42 Wet techniques such as liquid or size-exclusion chromatography 43,44 and high-speed centrifugation 45 provide limited SWNT separation from other forms of carbon. Still, the primary obstacle for nanotube purification is removal of residual metal catalyst particles that embed between the SWNTs; these particles are more stable than nanotubes and are therefore difficult to remove.…”
Section: Purification Of Swntsmentioning
confidence: 99%
See 1 more Smart Citation
“…One efficient dry purification technique is oxygen burning, or annealing, in which oxygen gas preferentially oxidizes both amorphous carbon and sp 3 -hybridized carbon nanoparticles, which are more reactive than sp 2 -hybridized SWNTs. 41,42 Wet techniques such as liquid or size-exclusion chromatography 43,44 and high-speed centrifugation 45 provide limited SWNT separation from other forms of carbon. Still, the primary obstacle for nanotube purification is removal of residual metal catalyst particles that embed between the SWNTs; these particles are more stable than nanotubes and are therefore difficult to remove.…”
Section: Purification Of Swntsmentioning
confidence: 99%
“…27 Removal of the catalyst is usually accomplished with a nitric acid reflux, which also eradicates any remaining superfluous carbon. 41,[46][47][48] Although dry and wet purification methods remove the majority of residual carbon and metal catalysts, it is important to note that some residual impurities remain in all current SWNT samples.…”
Section: Purification Of Swntsmentioning
confidence: 99%
“…It should be noted that the burning temperature of the K 2 S 2 O 8 -treated CarboLex SWNTs sample increases in comparison with the starting materials. This is a result of partial removal of metal catalysts [11] as verified by the smaller amount of residue at 900 8C than that of the as-prepared SWNTs sample. In summary, K 2 S 2 O 8 oxidation plays roles in modifying, unbundling and coating SWNTs, along with partial removal of amorphous carbon and metal catalysts.…”
Section: Chemical Modifications Of Swntsmentioning
confidence: 82%
“…Since metal catalytic particles are always found encapsulated in PCNs, the accessibility of acids to them is a severe problem. It has been reported that exposure to moist air or wet Ar/O 2 mixture [11], ultrasonic suspension with inorganic nanoparticles [12], ozone oxidization [13], and microwave treatment [14,15] can breach the surrounding carbon shell to some degree. But, under these severe conditions further damage on the remaining walls of SWNTs inevitably took place.…”
Section: Introductionmentioning
confidence: 99%
“…N- As-prepared CNTs contain carbonaceous impurities, such as amorphous carbon and graphite nanoparticles, and particles of the transition-metal catalysts (see Note 2). The use of high-temperature oxidation in air is effective in removing amorphous and graphitic contaminants from MWCNTs; for SWCNTs, however, metal catalysts must first be removed before this oxidation step since such metals are known to catalyze the low-temperature oxidation of CNTs (12,13). In principle, the purification of SWCNTs is feasible by using a combination of the following: gas-or vaporphase oxidation; wet-chemical oxidation/treatment; and centrifugation or filtration (including chromatography techniques) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: -Pyrenebutanoic Acid Succinimidyl Ester (Pase)mentioning
confidence: 99%